Steroid Compounds from Sida szechuensis - Li, Wei-Feng; Wang, Ya-Ling; Gao, Yun-Tao; Li, Jing; Song, Qi-Shi (Asian Journal of Chemistry, 2014)
A new steroid compound, 2b,3b,14a,20,21,22R,24-heptahydroxycholest-7-en-6-one (1), was isolated from Sida szechuensis. Its structure was determined by spectroscopic analysis, including extensive 1D and 2D-NMR data. Ten previously known compounds were also identified i.e., 3-O-b-D-glucopyranoside-a-ecdysone, loliolide, 3-O-b-D-galactopyranoside-b-ecdysone, 3,4,5,6-tetrahydro-3-methyl-b-carboline-5-carboxylic acid, b-ecdysone, polypodine B, a-ecdysone, b-sitosterol, astragalin 6"-O-(4-hydroxycinnamoyl) and pterosterone. The antibacterial assay of the new compound showed that it has inhibitory effect on Escherichia coli with a concentration of 20 mg/mL.